Rapid weight loss practices in elite kickboxers - Dugonjic, B.; Krstulovic, S.; Kuvacic, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The aim of this observational cross-sectional survey was to determine the prevalence of rapid weight loss (RWL) in elite kickboxers. Kickboxers (61 males; age = 24.2 ± 4.6 years, weight = 73.9 ± 12.8 kg, and height = 179.2 ± 7.9 cm) from eight European countries completed a Rapid Weight Loss Questionnaire regarding prevalence, magnitude, and methods of RWL. All athletes (100%) were practicing RWL before the competition with a Rapid Weight Loss Questionnaire score of 52.4 ±12.9. Most kickboxers `usually lose between 2% and 5% of their body mass, whereas ~30% lose between 6% and 8%. However, it is alarming that almost 30% reported cutting 10% of body weight or more sometime during their kickboxing career. Almost half of the athletes always practice gradual dieting (45.9%) and increased exercising (44.3%) to reduce body mass. Kickboxers usually reduce weight three to four times during a year, usually 7-15 days before a competition. More than a third (34.4%) started with RWL practice under the age of 17. There was no significant difference between weight divisions in weight management behaviors (p = .5, F = 0.6; Eta2 = .0) and no relation between the main characteristics of elite kickboxing athletes and the total RWL score. In conclusion, RWL practices in kickboxing athletes are somewhat specific and different when compared with other combat sports, which can be explained by greater number of weight classes and specific weigh-in protocol.